1H‐NMR Characterization of Epoxides Derived from Polyunsaturated Fatty Acids. (12th February 2016) - Xia, Wei; Budge, Suzanne M.; Lumsden, Mike D.
Abstract: In recent years, 1 H NMR has been used to study epoxides in lipid oxidation and industrial processes, but the peak assignments reported for monoepoxides and diepoxides have been inconsistent. Lack of clear assignments for chemical shifts of epoxides derived from polyunsaturated fatty acids (PUFA) has also limited the use of 1 H NMR in detecting and quantifying these products during both oxidative degradation and industrial epoxidation. In this study, 1 H NMR was used to characterize the epoxides synthesized from trilinolein, trilinolenin, canola oil, and fish oils by reaction with formic acid and hydrogen peroxide. Assignments for epoxides derived from PUFA in canola oil and fish oil were between 2.90–3.23 ppm and 2.90–3.28 ppm, distinct from other chemical groups in these oils. Chemical shifts of epoxy groups moved downfield with an increasing number of epoxy groups in the fatty acid chain. Hence, peaks for diepoxides appeared at 3.00, 3.09, and 3.14 ppm and for triepoxides at 3.00, 3.16, and 3.21 ppm. Results also suggested that stereoisomers of diepoxides and triepoxides were formed during the epoxidation process under the conditions of this study. These new assignments for di‐ and tri‐epoxide stereoisomers were supported by GC–MS analysis of their methyl esters, H–H COSY experiments, and a re‐evaluation of several previous epoxide‐related studies.